2012
DOI: 10.1111/j.1751-7176.2012.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplements and Hypertension: Potential Benefits and Precautions

Abstract: J Clin Hypertens (Greenwich). 2012; 14:467–471. ©2012 Wiley Periodicals, Inc. Dietary supplements (DSs) are used extensively in the general population and many are promoted for the natural treatment and management of hypertension. Patients with hypertension often choose to use these products either in addition to or instead of pharmacologic antihypertensive agents. Because of the frequent use of DS, both consumers and health care providers should be aware of the considerable issues surrounding these products a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 20 publications
(42 reference statements)
1
24
0
Order By: Relevance
“…3,4 Several dietary supplements are currently marketed for the management of hypertension, but the evidence for effectiveness is conflicting. 5 One such supplement thought to have an antihypertensive effect is chlorogenic acid (CGA).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Several dietary supplements are currently marketed for the management of hypertension, but the evidence for effectiveness is conflicting. 5 One such supplement thought to have an antihypertensive effect is chlorogenic acid (CGA).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the BP lowering effect of garlic, two systematic reviews and metaanalyses showed that garlic was better than placebo in reducing the BP, 21,22 whereas its cholesterol-lowering properties were no better than placebo. 23 In their review of the subject, Rasmussen et al 24 state that based on the inconsistencies of the effect of garlic on BP, it is difficult at this time to recommend its use for the treatment of HTN. With respect to drug interactions, the administration of garlic in patients with CVD receiving anticoagulants should be avoided for the danger of bleeding, because of its platelet antiaggregatory effects.…”
Section: St John's Wort (Hypericum Perforatum)mentioning
confidence: 98%
“…Although, pharmacists advised caution in hypertensive patients because it has been documented to cause increase in blood pressure, tachycardia, and palpitations (Rasmussen et al, 2012). Elevated serum digoxin levels were reported in a patient taking digoxin and Siberian ginseng (McRae, 1996), but the case was debatable, the critics suggesting a possible botanical misidentification by clinical investigators (Awang, 1996).…”
Section: Safetymentioning
confidence: 99%